The Introduction of Uk Rockbolting Technology into Coal MinesAround the World - Graham Daws (International Conference on Ground Control in Mining, 2011)
The introduction of UK rock bolting technology has been applied in many large underground coal mines around the world. This paper explains the methods that have been applied for its successful introduction and discusses several case studies. It does not give fine detail but is intended to allow decision makers to gain a basic understanding of the method used to introduce rock bolting to a mine.